Modification of Thin-Film Polymer Membranes by Microwave Radiation in Ammonia Medium - D. Fazullin, Dinar; A. Kharitonova, Elena; V. Mavrin, Gennady (International Journal of Engineering and Technology, 2018)
In this paper, we aimed to modify thin-film microfiltration membranes of nylon and polytetrafluoroethylene (PTFE) with ultrahigh-frequency (UHF) radiation within the decimeter wave band in ammonia vapor medium. It has been found that the treatment of a nylon membrane in ammonia leads to the membrane capacity decrease from 79% to 70.8% and to membrane weight decrease by 0.52%. And they observed the decrease of membrane weight by 0.24% from the original. In general, the treatment of membranes with microwave radiation in ammonia medium leads to specific productivity increase. They revealed the decrease of emulsion separation degree after the nylon membrane treatment by microwave radiation in ammonia environment. And when the oil emulsion is separated using PTFE-treated membranes, the degree of purification from oil increases by 3.6%, and the size of the separated oil particles also decreases from 118 nm to 49 nm.Â Â